SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BONUS PADA PT. PLN TULUNG KLATEN (Information Technology and Telematics, 2013)
Administration of the human resources of a company affects many aspects of employee performance is a critical success. For those in need of employee data that every time an increasing number of data which includes employee data, work history, education history, family data and power to enhance human resources. The information was obtained from data data tersebutsangat influence the decision-making process for awarding bonuses. Destination that will accomplish is to make the decision support system that can help the decision makers to determine bonuses based on the performance of employees at PT. PLN Tulung Klaten using fuzzy logic gap analysis. The results of this research are decision support systems that can be made to support PT. PLN Tulung Klaten in knowing that employees deserve a bonus research performance with standard values ​​bobotdan telanh assessment guidelines specified. Keyword SPK, PT. PLN Tulung Klaten, Fuzzy Logic gap analysis